Pembrolizumab for patients with melanoma or non-small-cell lung cancer and untreated brain metastases: early analysis of a non-randomised, open-label, phase 2 trial. Issue 7 (July 2016) - Goldberg, Sarah B; Gettinger, Scott N; Mahajan, Amit; Chiang, Anne C; Herbst, Roy S; Sznol, Mario; Tsiouris, Apostolos John; Cohen, Justine; Vortmeyer, Alexander; Jilaveanu, Lucia; Yu, James; Hegde, Upendra; et al.
Summary: Background: Immunotherapy targeting the PD-1 axis has activity in several tumour types. We aimed to establish the activity and safety of the PD-1 inhibitor pembrolizumab in patients with untreated brain metastases from melanoma or non-small-cell lung cancer (NSCLC). Methods: In this non-randomised, open-label, phase 2 trial, we enrolled patients aged 18 years or older with melanoma or NSCLC with untreated brain metastases from the Yale Cancer Center. Patients had at least one untreated or progressive brain metastasis between 5 and 20 mm in diameter without associated neurological symptoms or the need for corticosteroids. Patients with NSCLC had tumour tissue positive for PD-L1 expression; this was not required for patients with melanoma. Patients were given 10 mg/kg pembrolizumab every 2 weeks until progression. The primary endpoint was brain metastasis response assessed in all treated patients. The trial is ongoing and here we present an early analysis. The study is registered withClinicalTrials.gov, numberNCT02085070 . Findings: Between March 31, 2014, and May 31, 2015, we screened 52 patients with untreated or progressive brain metastases (18 with melanoma, 34 with NSCLC), and enrolled 36 (18 with melanoma, 18 with NSCLC). A brain metastasis response was achieved in four (22%; 95% CI 7–48) of 18 patients with melanoma and six (33%; 14–59) of 18 patients with NSCLC. Responses were durable, with all but one patient with NSCLC who responded showing an ongoing response at the time of data analysis on June 30, 2015. Treatment-related serious and grade 3–4 adverse events were grade 3 elevated aminotransferases (n=1 [6%]) in the melanoma cohort, and grade 3 colitis (n=1 [6%]), grade 3 pneumonitis (n=1 [6%]), grade 3 fatigue (n=1 [6%]), grade 4 hyperkalemia (n=1 [6%]), and grade 2 acute kidney injury (n=1 [6%]) in the NSCLC cohort. Clinically significant neurological adverse events included transient grade 3 cognitive dysfunction and grade 1–2 seizures (n=3 [17%]) in the melanoma cohort. Interpretation: Pembrolizumab shows activity in brain metastases in patients with melanoma or NSCLC with an acceptable safety profile, which suggests that there might be a role for systemic immunotherapy in patients with untreated or progressive brain metastases. Funding: Merck and the Yale Cancer Center.